A TOOL FOR THE PROFESSIONAL DEVELOPMENT OF FUTURE HIGHER EDUCATION ENGLISH TEACHERS - Abdurashidova, Nilufar (Журнал иностранных языков и лингвистики, 2023)
In our article, the problem of organizing the educational process using different types of alternative assessments of student activities will be considered. This type of assessment allows you to organize the interaction between a group of students and teachers within the framework of conditions closest to the state of real teacher-student communication and contribute to the formation of the skills and abilities necessary for the effective implementation of professional pedagogy required activity in the future.